ANALYSIS MODEL IN DATA COMMUNICATION - Lias Antono; Aqwam Rosadi Kardian., SKom, MM (Jurnal Sistem Komputer, 1998)
When you want high-speed modem is recommended selecting a modem that uses standard signal V.32/V.32 bis, V.42 error control standards and strandar V.32 bis data compression. V.32 bis modem speed bps bps can transfer a file, which means we can save a lot of telephone fee. In choosing a variety of supporting hardware and software, the author has been outlined previously and has been clear that the selection of hardware and software support is very important as adjusted for the usefulness of the modem itself. Benefits and constraints are also factors must be considered, this will facilitate the workings of a modem in accordance with our needs as a user.